Increasing resilience through nudges in the urban water cycle: An integrative conceptual framework to support policy decision-making. (March 2023) - Poch, Manel; Aldao, Carolina; Godo-Pla, Lluís; Monclús, Hèctor; Popartan, Lucia Alexandra; Comas, Joaquim; Cermerón-Romero, Manuel; Puig, Sebastià; Molinos-Senante, María
Abstract: Relevant challenges associated with the urban water cycle must be overcome to meet the United Nations Sustainable Development Goals (SDGs) and improve resilience. Unlike previous studies that focused only on the provision of drinking water, we propose a framework that extends the use of the theory of nudges to all stages of the overall urban water cycle (drinking water and wastewater services), and to agents of influence (citizens, organizations, and governments) at different levels of decision making. The framework integrates four main drivers (the fourth water revolution, digitalization, decentralization, and climate change), which influence how customers, water utilities and regulators approach the challenges posed by the urban water cycle. The proposed framework, based on the theory of nudges first advanced by the Nobel Prize in behavioral economics Richard H. Thaler and Cass R. Sunstein (Thaler and Sunstein, 2009), serves as a reference for policymakers to define medium- and long-term strategies and policies for improving the sustainability and resilience of the urban water cycle. Finally, we provide new insights for further research on resilience approaches to the management of the urban water cycle as an element to support the more efficient formulation of policies. Graphical abstract: Image 1 Highlights: This framework extends the use of nudges to the overall urban water cycle. It considers 4th water revolution, digitalization, decentralization, climate change. It could be used by decision-makers in transit to a sustainable urban water cycle.